MODEL STRUKTURAL PEMASARAN MEDIA SOSIAL DALAM MENINGKATKAN PEMBELIAN PRODUK MATERNAL DISASTER - Raymond Bagas Dhani Agustin; Mochamad Nurhadi; Ronny Ronny (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
The presence of various local and international fashion brands makes the competition in the fashion industry tighter. Maternal Disaster as one of the local fashion brands continues to strive to maintain its existence amidst changing trends and consumer preferences. This study aims to analyze the structural model of social media marketing strategies used to increase brand love, brand awareness, brand trust, and brand loyalty that make people make first-time purchases and have positive traits so that they will experience repeat purchases (Repurchase Intention) of Maternal Disaster brand local clothing products. The research population involved customers of Maternal Disaster brand local clothing products in major cities, with data collected from 186 respondents via Google Form questionnaire using a purposive sampling technique. Variables were measured with a Likert Scale, and data analysis was conducted using PLS-SEM through measurement and structural model evaluation. The results show that although marketing on social media does not directly increase the number of customers who ultimately purchase Maternal Disaster, it can increase repeat purchases through increased loyalty and love for the brand. In addition, it increases brand trust and brand awareness, which are paramount to increasing repeat purchases.